Food Labeling: Analysis, Understanding, and Perception (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue includes original research and reviews of the literature focusing on food labels, which are a tool to promote public health that, at the same time, may represent a marketing tool and may influence consumers’ perception of food quality.